Effect of soaking time to the bending strength of porcelain with palm oil fuel ash - Noh, Mohamad Zaky; Jamo, Hassan Usman; MUHAMAD NOR, Mohd Al Amin; AHMAD, Zainal Arifin (Unique Research Publications, 2018)
Silica from a treated palm oil fuel ash (POFA) was used as a substitute material in producing an improved porcelain ceramics. POFA was grounded in a ball mill until the median particle size was reduced to about 50 μm. It was heated at 600 ºC for 1.5 hours in an electric furnace. Then it was substituted quartz in porcelain composition from 5 wt.% up to 25 wt.%. The mixed powder was pressed into pellets at pressure of 91 MPa. All the pellets were sintered at 1100 ºC for the soaking times of 1 hour, 2 hours and 3 hours, respectively. It clearly indicated that the bending strength of the samples increases with the increase in POFA substitution and the increase in soaking time. With a value of 45 MPa bending strength of the samples containing 15 wt.% of POFA and sintered at a soaking time of 2 hours is the highest. This could be attributed from the increase in mullite and sharp microstructural changes. Porcelain containing POFA has about 7% weight reduction compared to the standard porcelain.